Heredity and Otosclerosis: A Review - Greval RS; Bhagat Singh (Journal of All India Institute of Speech and Hearing, 1970)
A  genealogical tree is presented of a family in which the dominant heredity of clinical otosclerosis was traced through three generations. Recent hypotheses   for    hereditary  transmission of  the  disease have been advanced and evaluated. Chromosomal  changes in otosclerotic subjects have been found by different workers to be conspicuously  absent. Therefore the most convenient,  and  practical,  way of  ascertaining the exact mode of genetic ransmission in otosclerosis is through large-scale family studies. This particularly holds good  for a vast country like India. The most recent genetic studies in the field indicate a polygenic and  probably   multifactorial mode of  heredity of otosclerosis.